ANALISIS TEORITIS LAYER METHOD DAN EKSPERIMENTAL PERKUATAN BALOK BETON BERTULANG MENGGUNAKAN TULANGAN LONGITUDINAL DENGAN SELIMUT MORTAR - Nursiah Chairunnisa (Universitas Lambung Mangkurat, 2011)
Strengthenning and Retrofitting methods already had applicated in buildings. Beam is One of structure elements can be strengthenned in order to maintain efficient serviceability structure that can be caused change of function from structures likes overloading or lack of quality control at construction so it can fulfill the code of structures to day and future. This research had to know about effectiveness strengthening methods of reinforced concrete beams using longitudinal compression and tension reinforcement with jacketing mortar as flexural strengthening and had to know effectiviness of theoritical methods for interpreting result . In this research specimen models consist of four specimens: one was control beam (BK), one was monolith beam (BM) and one was strengthened beam (BP)without bonding agent and BP2 was strengthenned beam with bonding agent . All beams were tested under 2-point loading midspan as flexural load and also instrumented for the measurement of mid-span deflection and crack pattern. Test result were compared to analytical method and program computer based layer method (software Response-2000). The result shows performanced of Response-2000 as layer method an theoritical methods provided equal performances if compared with experimenta method. It can be shown that the percentags of Ultimate Load between Response 2000 with experimental method was 107 % -109% for BK, 110,42-111,40% for BM , 83,77% - 83,81% forBP1 dan 87,66-87,70 for BP2. Failure patterns of the control beam (BK) and monolithical beam (BM) were flexural while the strengthened beams had debonding. At this researched, an analythical method (Response-2000)also presented equal performance at failure patterns. It can be shown two specimens (BK and BM) were flexural failured an others (BP1 and BP2) were debonding failured too.